PENGARUH METODE “BRISK WALKING EXERCIXE” TERHADAP PENURUNAN TEKANAN DARAH PADA PASIEN HIPERTENSI DI UPT PELAYANAN SOSIAL LANJUT USIA KISARAN RANTAU PRAPAT TAHUN 2020 - Niasty Lasmy Zaen; Fitri Sinaga (Jurnal Ilmiah Kebidanan Imelda, 2020)
Blood pressure is the pressure that is urged by circulating blood in the walls of blood vessels, and is one of the vital signs of the principal technique in reducing blood pressure Brisk walking exercise. blood pressure in hypertensive patients at UPT Elderly Social Services Range in Prapat Overseas Range in 2020. This study used a pre-experimental design study One Group pre-test and post-test design. The population in this study were all elderly who had hypertension in the UPT Elderly Social Services Range in 2020, as many as 50 elderly people using the Purposive Sampling technique in which the research sample was 40, the statistical analysis of the data used in this study was univariant and bivarian namely using the Wilcoxon Test. Based on the results of the study there was a significant effect between blood pressure before and after the Brisk Walking Exertice, with a p value (0,000) <α (0.05). For further researchers can improve and pay attention to the number of sex characteristics and pay more attention to the procedures given. Future researchers can also compare brisk walking exercise techniques with other aerobic sports. Keywords : Hypertension, smoking, Brisk Walking Exercixe